Analysis of water quality in watershed using heavy metal pollution index - Rizky Muliani Dwi Ujianti; Mega Novita; Aan Burhanuddin; Iffah Muflihati; Lukman Anugrah Agung; Roies Nur Ingsan; Alfan Najihil Wafa; Cerly Nurlita Anggraeni; Tsaqif Muzakki (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
The quality of rivers and coastal is gradually deteriorating along with rapid population and socio-economic growth in the watershed to the estuary. Sampling was conducted in Semarang city rivers and Demak district rivers, Central Java Province, Indonesia, at four different stations according to geography and designation: river basins, estuaries, and rivers affected by industrial and domestic waste. Research time is August - October 2023 during the dry season. The research method uses descriptive analysis to determine the variables to be studied based on the research results in the field. River and coastal pollution levels are measured using the Heavy Metal Pollution Index method, with several water quality parameters measured, such as BOD, COD, Ammonia, TDS, TSS, and Total Coliform. In contrast, the heavy metal parameters measured are Cd, Ni, Zn, Cu, and Pb. The heavy metals and water quality parameters analyzed guided by Government Regulation of the Republic of Indonesia Number 22 of 2021 class 2. Water quality and heavy metal analysis use the Heavy Metals Pollution Index (HPI). HPI is an assessment method that shows the influence of individual heavy metal compounds on overall water quality. The results show that the status of non-metal water quality in terms of HPI analysis shows that Sampling Station (SS) 1 is 224.30 (unsuitable for drinking), SS 2 is 645.98 (unsuitable for drinking), SS 3 is 320.09 (unsuitable for drinking), SS 4 is 252.09 (unsuitable for drinking), and metal parameters in terms of HPI analysis show that SS1 is 26.43 (good), SS2 is 2345.84 (unsuitable for drinking), SS3 is 26.43 (good), and SS4 is 12.64 (excellent). The conclusions from these four research areas indicate that the status of water quality, according to the HPI is unsuitable for drinking, however, indications of heavy metals in 2 areas are still tolerable, namely good and excellent. The decline in water quality in the research area is caused by domestic and industrial waste polluting the waters. In conclusion, this river area requires further management from the collaboration of various stakeholders.Keywords:Water QualityHeavy MetalCoastalWatershed